Kesenjangan Sosial dan Ekonomi Masyarakat Daerah Terpencil: Studi Kasus Desa Pulau Maringkik - Tati Atmayanti; Muhammad Malthuf (Universitas Hamzanwadi, 2023)
Social and economic gaps include demographics, education, health, social capital, income, and the availability of economic support facilities, as well as infrastructure. The aim of this study is to describe the social and economic gaps in the community in the Village of Maringkik Island, East Lombok district of Nusa Tenggara West. This research uses a qualitative approach to this type of case study research. The primary data collection methods are non-participant observations, semi-structured interviews, and documentation. Data analysis uses Miles and Huberman analysis with interactive models and data validity testing with triangulation methods. Based on the results of the analysis, the existence of social and economic disparities in society, which is described in the form of socio-economic disparities, includes: social status of the community; education of the public; limitations of the mindset of conventional society; ownership of assets and incomes of the society; and limited public facilities. The causes of inequalities consist of social and economic changes; ancestral confidence; unmaximated village potential; still isolated areas; limited access to roads; and clean water. This gap affects poverty and limited employment opportunities in the Village of Maringkik Island